Analisis Faktor Penyebab Lost To Follow Up Pengobatan ARV (Antiretroviral) di Puskesmas Kencong - Septianingtyas Risti Anggraeni; Faiqatul Hikmah (Politeknik Negeri Jember, 2020)
The key to the success of HIV / AIDS treatment is ARV therapy. Continuous therapy can inhibit the spread ofHIV infection in the body and improve the quality of life of patients. Lost to follow-up is the absence of thepatient to return to the VCT clinic according to the date of the drug agreement and consultation. The KencongCommunity Health Center found a problem regarding lost to follow up. The cause of lost to follow upsuspected due to factors that can be related to Lawrence Green's theory such as presdiposing factors(knowledge, attitudes), enabling factors (patient books and help cards), and reinforcing factors (motivation,SOP). The purpose of this research was to analyze the factors that can cause lost to follow up antiretroviral(ARV) treatment in HIV patients in Kencong Health Center. The type of this research was qualitative and thisresearch used 6 patients, 1 counselor and 1 doctor as respondent. The results of this research shows that theknowledge of patients is still lacking, especially way of virus transmission and the side effects caused and thelocation of the HIV virus in the body, meanwhile scheduling knowledge of patient is good. Respondents have apositive attitude towards ARV treatment. The book which use to record the patient’s visit data has beendeemed capable to control the arrival of patient. There are still many patients who don't carry a patient cardwhen they want to take medicine. Counselors and doctors have provided the best motivation during thecounseling process. Kencong Puskesmas still does not have SOP about lost to follow up